2003
DOI: 10.2174/1568007033482805
|View full text |Cite
|
Sign up to set email alerts
|

GABAC Receptors as Drug Targets

Abstract: GABA(C) receptors are the least studied of the three major classes of GABA receptors. The physiological roles of GABA(C) receptors are still being unravelled and the pharmacology of these receptors is being developed. A range of agents has been described that act on GABA(C) receptors with varying degrees of specificity as agonists, partial agonists, antagonists and allosteric modulators. Pharmacological differences are known to exist between subtypes of cloned GABA(C) receptors that have been cloned from mamma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
67
1

Year Published

2006
2006
2018
2018

Publication Types

Select...
5
2
2

Relationship

0
9

Authors

Journals

citations
Cited by 80 publications
(69 citation statements)
references
References 84 publications
1
67
1
Order By: Relevance
“…To date, 16 different GABA A subunit isoforms have been identified (excluding the GABA C receptor subunits ρ1-ρ3), and a large number of functional hetero pentamers have been described. [3][4][5] Several studies with animal models have revealed distinct pharmacological effects that are specifically mediated by different receptor isoforms. 6 These findings have spurred a race for the development of novel ion channel modulators showing specificity restricted to distinct isoforms and thus, it is hoped, circumventing well-known side effects of current GABA A R drugs, such as sedation, ataxia, cognitive impairment, amnesia, and potential for abuse.…”
mentioning
confidence: 99%
“…To date, 16 different GABA A subunit isoforms have been identified (excluding the GABA C receptor subunits ρ1-ρ3), and a large number of functional hetero pentamers have been described. [3][4][5] Several studies with animal models have revealed distinct pharmacological effects that are specifically mediated by different receptor isoforms. 6 These findings have spurred a race for the development of novel ion channel modulators showing specificity restricted to distinct isoforms and thus, it is hoped, circumventing well-known side effects of current GABA A R drugs, such as sedation, ataxia, cognitive impairment, amnesia, and potential for abuse.…”
mentioning
confidence: 99%
“…Using this as a template, computer-generated models of ligandbinding pockets of Cys loop receptors, combined with previous data from structure-activity studies, have identified important features of these pockets and on the orientation of agonists and antagonists when located in their binding sites (7)(8)(9)(10)(11)(12)(13). Generating an accurate representation of the orientation of GABA in the GABA C receptor-binding site could identify the processes involved in ligand recognition at this receptor and would also assist in drug design; current data indicate that drugs acting on GABA C receptors could possibly be used to treat visual, sleep, and cognitive disorders (4,14).It has recently been shown that Tyr-198 forms a cationinteraction with the positive amine of GABA (15), and thus we can confidently locate this part of the GABA molecule close to this residue. The aim of this study was to locate the other end of GABA, the carboxylate group, in the binding site.…”
mentioning
confidence: 99%
“…They are homomeric rather than heteromeric and therefore much simpler receptors. These properties make them important drug targets [42].…”
Section: Tpmpa and Related Compounds Competitive Antagonists Of Gabamentioning
confidence: 99%